How Do Villagers Solve Their Legal Problems? A Study of District Court (Peradilan Desa) for Dispute Settlement Process - Wahanisa, Rofi; Lestari, Dwi; Rahman, Malik Akbar Mulki; Putri, Fadhilah Rizky Aftriani (Indonesian Journal of Advocacy and Legal Services, 2021)
This study aims to provide another alternative in resolving conflicts in Lerep Village which is called the District Court (Peradilan Desa). The village court aims to help resolve conflict problems in Lerep Village so that there is no accumulation of cases in the surrounding District Courts. Village justice is carried out by familial mediation between the person in dispute with the head of the local hamlet and the village head. The decisions given are in the form of suggestions from the hamlet head and village head which are not binding. District justice (Peradilan Desa) is a win-win solution to the conflict in Lerep Village. However, the implementation of this District court still has shortcomings. One of them is the district court does not yet have a reference for regulations in its implementation. Another deficiency is the lack of knowledge in the legal field of the parties acting as intermediaries, such as the hamlet head and village head. The research method used in this research is legal research, legal research is often referred to as doctrinal or normative. Normative legal research examines principles, numbers, concepts, rules, laws and regulations, research decisions, agreements and doctrines that are placed by law as a norm system by examining library studies. The conclusion in this study is that specific regulatory references are needed to regulate the running of village courts. And there must be training to provide basic knowledge to the parties concerned.